ORIENTASI PELANGGAN PADA PEMASARAN PELAYARAN NIAGA (Study Empirik terhadap Perilaku Chaterer pada Pasar Kapal Tramper dan Liner) - Suwarno Suwarno (UNIMAR AMNI Semarang, 2015)
Marketing of shipping companies is not only concerned with the development and implementation ofsuccessful strategies. For marketing to be successful there needs to be a marketing orientation throughout thecompany which fosters the marketing concept and demonstrates a marketing approach to all internal and externalactivities. The concept of customer orientation in business markets has attracted attention from bothacademics and managers and it has been widely used in the marketing discipline. The term customer orientedfirms is used to describe how knowledgeable the firm is about the clients’ needs and how responsive the firm is tothem in terms of the continuous value creation and delivery. Despite the increasing literature being focused oncustomer orientation and business relationships in general, there is a lack of literature explaining the marketingorientation in shipping companies. Shipping marketing can be described by means of all practical aspects withina marketing program, such as market analysis, segmentation, planning, differentiation, positioning, promotionand transport service production. A marketing orientation is based around a philosophy, which places the chartererand shipper first, and it recognizes that every action taken by the shipping company ultimately affects thecustomer relationship. Therefore, a necessary precondition of an effective shipping marketing is the understandingof the different needs the charterers and shippers have within the different market segments. The weakness ofunderstanding the needs the client groups have, leads to the weakness of correct marketing planning and to thefailure of providing the desired transport services. The article begins with a brief discussion and definitions forthe marketing of shipping companies. Then, the framework of customer orientation in shipping companies isanalyzed. The paper is based on an empirical research, which concerns the buying behavior in the tramp andliner market. Consequently, the psychology and buying behavior of a shipping company’s clients are examined,as well as the charterers’ and shippers’ transportation needs, decision processes and the factors influencing them.The paper concludes with a discussion of the findings in terms of the implications for both theory and shippingpractice.Keywords : Marketing of shipping companies; customer orientation; marketing discipline; tramp and linermarket.